ANALISIS PENGUKURAN KINERJA PELAKSANAAN ANGGARAN MENGGUNAKAN IKPA - Sodikin Sodikin (JENTRE, 2021)
The Ministry of Finance establishes The Budget Implementation Performance Indicator (IKPA) to measure the performance of ministries or agencies’ budget management. IKPA also functions as an evaluator monitoring media that can provide an assessment of budget implementation in a work unit (satuan kerja) which has implication for better state financial management. Descriptive statistical methods, Likert scale, and Qualitative methods are used in this study to analyze the planning with budget execution suitability, budget implementation effectiveness, and also constraints faced by work units in Bandung area on the process of measuring performance through IKPA. Based on the data collection and analysis from 28 respondents, it was found that the effectiveness of budget implementation and the planning with budget suitability realization were in good value, yet in line with several obstacles the units faced. The encountered constraints demand the units to require a distinct calendar of work unit activities in one fiscal year which is the basis for determining the plan for withdrawing funds. It has an impact on budget absorption and work unit achievement as well.